Analysis Comparative of Halal Literacy Levels and Halal Awareness Index Towards the Consumption of Halal Food Products among Muslims in Sorong City, Southwest Papua - Wangsi, Mitta Muthia; Wally, Nur Aeni; Talaohu, Mundarain; Putri, Nur Aulia (Universitas Muhammadiyah Sorong, 2025)
The aim of this study is to examine Muslims in Sorong city's halal literacy and halal awareness index with regard to halal product consumption. This research is a particular kind of quantitative study that employs a normative method. The present study employs a statement item instrument as its data collecting method. The instrument is structured according to halal literacy characteristics and the halal awareness index. The data is analyzed using SPSS version 26 and the Halal Awareness Index is computed. The sample size for this study is 102 Muslim customers from Sorong city, representing the Muslim community in the city. This research uses purposive sampling technique, which is a non-probability sampling method. This research shows that halal literacy has a positive and significant impact on the consumption of halal food products among Muslims in Sorong, Southwest Papua. The Halal Awareness Index also has a positive and significant effect on the consumption of halal food products among Muslims in Sorong, West Papua. This is further supported by the calculation results of the Halal Awareness Index, where Muslims in Sorong